Dampak Pemanasan Global Terhadap Lingkungan Hidup Di Kota Medan: Tinjauan Terhadap Kebijakan Mitigasi Dan Respon Masyarakat - Aprianta Tarigan; Asha Yatri Saragih; Rahma Yani Hasibuan; Risa Elvina Nasution; Riska Marpaung; Vebri Meliarni Oktavia Naibaho; Yunita Manurung (Universitas Palangka Raya, 2024)
Global warming is a serious challenge for cities throughout the world, including the city of Medan. In this context, this research aims to investigate the impact of global warming on the environment and society of Medan City. Through a qualitative approach, data was collected through interviews and observations of the community as well as analysis of government policies related to this problem. The research results show that global warming has caused an increase in air temperature, air pollution, a decrease in ecosystem quality, and an increase in the volume of waste in Medan City. In addition, public health risks are also increasing, and cities are becoming more vulnerable to natural disasters. Based on these findings, effective mitigation and adaptation measures are needed to overcome the impacts of global warming. Active participation from governments, NGOs and civil society is also critical in achieving this goal. This research concludes that public awareness and participation can be increased through education, outreach campaigns, and innovative approaches, which in turn will help Medan City move towards a more sustainable future.